Passive mode-locking in single tapered diode laser / Mohd Kamil Abd Rahman - Abd Rahman, Mohd Kamil (Faculty of Applied Sciences, 2004)
Passive mode-locking was demonstrated in a monolithic single contact tapered diode laser without a separate saturable absorber section. Pulsewidths of 0.86 ps have been achieved at a repetition rate of 116 GHz, with average power of about 8 mW. It is believed that physical mechanisms of the laser, which is due to the nature of the taper, are the cause of the modelocking operation. Thus, mode-locked pulses are conveniently obtained in a much simpler technique compared to multi-section lasers. Moreover the laser can also be mounted as pside down for effective heat-sinking.